Preferences for Income Redistribution in Unequal Contexts: Changes in Latin America Between 2008 and 2018 - Franetovic, Gonzalo; Castillo, Juan-Carlos (Frontiers in Sociology, 2022)
In a developing and highly unequal region like Latin America, it is crucial to understand the determinants that affect people’s support for redistribution of resources from the state. A series of theories focused on self-interest have continuously established a negative link between people’s income and their support for the reduction of inequalities through redistribution. Despite this, the evidence is scarce and sometimes contradictory while its study in Latin America is almost non-existent. Using data from the LAPOP Survey between 2008 and 2018, a longitudinal dimension is considered for the first time in the measurement of Latin American redistributive preferences, using hybrid multilevel regression models. In contrast to the evidence from studies conducted in other regions, the results reveal that in Latin America it is not possible to detect a clear association between income and redistributive preferences at specific times, but it is possible when changes occur in countries’ levels of inequality and economic development. Likewise, other elements that consistently affect preferences are evident, such as educational level, political ideology, and confidence in the political system. In light of this evidence, comparisons are made with previous research findings in industrialized countries, challenging rationalist theories of justice and solidarity.